5(2.6x+3.9)=5

Simple and best practice solution for 5(2.6x+3.9)=5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(2.6x+3.9)=5 equation:


Simplifying
5(2.6x + 3.9) = 5

Reorder the terms:
5(3.9 + 2.6x) = 5
(3.9 * 5 + 2.6x * 5) = 5
(19.5 + 13x) = 5

Solving
19.5 + 13x = 5

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-19.5' to each side of the equation.
19.5 + -19.5 + 13x = 5 + -19.5

Combine like terms: 19.5 + -19.5 = 0.0
0.0 + 13x = 5 + -19.5
13x = 5 + -19.5

Combine like terms: 5 + -19.5 = -14.5
13x = -14.5

Divide each side by '13'.
x = -1.115384615

Simplifying
x = -1.115384615

See similar equations:

| cos(2x)-5cosx+3=o | | .5x+7=2x+14 | | 1-4=7 | | 18-8(x+2)=2(x-9) | | 3x+5=-6x+32 | | -2/5(5x-20y) | | 2x^2+8x+n=15+n | | -(ln)(2)/x=91.2 | | F(x)=x^4+6x^3+9x^2 | | x+7*2=122 | | x+7*2= | | 3n^2+4n-4=0 | | -4/3(33=n)=12=n | | 10x-30=10 | | x+2*(x+2+2x-8)=x+1*(x+1+2x-5) | | 14x-14-4+6=0 | | (3x-1)-5(x+2)(x-2)+12=6+(2x+3) | | x^2+2xy+y^2=0ratio | | 3n^2+3n-36=0 | | 3k+16=5k+20 | | -10a+25a+5a=-40 | | f=9*6 | | 37=5a-4a-3 | | 3x^2-25x-28= | | 7x(2x+3)=0 | | f=9/6 | | 2(n+4)-(3n+1)=5 | | 3500=(x-.20x) | | x^2=(x-2)*(x-2+(x+2)) | | x^2+4x-n^2=0 | | C=.0765x+0.06(0.765x) | | 3(2x-1)-2(3x-5)=7 |

Equations solver categories